Strengthening Religious Character Through the Tujuh Poe Atikan Program for Elementary School Students - Muhammad, Giantomi; Salma, Shofia Nurhumaira; Saepudin, Aep (Universitas Islam Sultan Agung, 2025)
Humans with character are a reflection of the progress of civilization. Everyone upholds the values of goodness and truth for the common good. Every religion wants goodness, especially Islam as a religion of the mercy of the universe. SDN 2 Tanjungsari, Purwakarta Regency, implements strengthening religious character through the Tujuh Poe Atikan program, namely a program that is based on the values of local wisdom of Sundanese culture. With that, it is hoped that Sundanese culture will be integrated in character formation efforts to strengthen religious character in students. The purpose of the study was to describe the implementation of strengthening religious character through the Tujuh Poe Atikan program for elementary school students. This study uses a qualitative approach with a case study method. Data sources were obtained from the Principal, Vice Principal and Teachers. Data collection techniques through interviews, observation and documentation. For data analysis techniques through data reduction, data completion, data interpretation, triangulation and conclusions. The results obtained show that strengthening religious character through the Tujuh Poe Atikan program in elementary school students strengthens religious character.